Association between long-term changes in obesity-related anthropometric indicators and the risk of type 2 diabetes mellitus in the older population - Xiaomin Xu; Lirong Li; Fengmei Chen; Zhirong Guo (Journal of International Medical Research)
Objective To investigate the association of long-term changes in body mass index, waist circumference, and waist-to-height ratio with the risk of type 2 diabetes mellitus in the older population. Methods We conducted a prospective cohort study in Jiangsu Province, China. Data from 593 participants who were aged ≥60 years were analyzed. The hazard ratios and 95% confidence intervals were estimated using the Cox proportional hazards model. Results Over a median follow-up period of 5.08 years, 70 participants (11.80%) developed type 2 diabetes mellitus. Compared with participants with persistently normal body mass index, waist circumference, and waist-to-height ratio, those in whom these parameters changed from normal to abnormal and those in whom these parameters were persistently abnormal had a significantly higher risk of type 2 diabetes mellitus, with adjusted hazard ratios of 2.11 (95% confidence interval: 1.05–4.26) and 2.37 (95% confidence interval: 1.21–4.63) for body mass index, 2.75 (95% confidence interval: 1.16–6.51) and 2.32 (95% confidence interval: 1.29–4.16) for waist circumference, and 2.24 (95% confidence interval: 1.14–5.91) and 4.11 (95% confidence interval: 2.21–7.68) for waist-to-height ratio, respectively. Conclusion Long-term changes in obesity-related anthropometric indicators are strongly associated with the risk of type 2 diabetes mellitus in the older population.